2013
DOI: 10.1007/s11783-013-0596-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the removal of monovalent and divalent cations in the microbial desalination cell

Abstract: Microbial desalination cell (MDC) is a promising technology to desalinate water and generate electrical power simultaneously. The objectives of this study were to investigate the desalination performance of monovalent and divalent cations in the MDC, and discuss the effect of ion characteristics, ion concentrations, and electrical characteristics. Mixed salt solutions of NaCl, MgCl 2 , KCl, and CaCl 2 with the same concentration were used in the desalination chamber to study removal of cations. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It might be due to the non-ideal characteristics of AEM near cathode, which might have diffused back the Na + ions from concentrate chamber toward cathodic chamber. Chen et al [32] reported that the ions may back diffuse through membrane due to concentration gradient and decreased electric field force with low current developed by the MDCs. Generally, when the substrate depletes, the current density of the system starts decreasing with increase in internal resistance.…”
Section: Ionic Composition Of Electrolytesmentioning
confidence: 99%
“…It might be due to the non-ideal characteristics of AEM near cathode, which might have diffused back the Na + ions from concentrate chamber toward cathodic chamber. Chen et al [32] reported that the ions may back diffuse through membrane due to concentration gradient and decreased electric field force with low current developed by the MDCs. Generally, when the substrate depletes, the current density of the system starts decreasing with increase in internal resistance.…”
Section: Ionic Composition Of Electrolytesmentioning
confidence: 99%
“…It was reported that the decrease of conductivity in saline solution increased the IR and thus decreased the overall cell potential of the MDC [8]. The IR was also affected by the intermembrane distance [56]. With inter-membrane distance of 0.30 cm, 1 cm and 1.50 cm, the corresponding IR was 342 Ω, 222 Ω and 214 Ω, respectively.…”
Section: Internal Resistance (Ir)mentioning
confidence: 97%
“…At lower ER values, the electrical current in theory is higher and thus can increase the desalination rate. Researchers demonstrated that when ER reduced from 1000 Ω to 10 Ω, the maximum current density and columbic efficiency increased by 680% and 275% respectively [56]. A continuously operated UMDC with 2 d of HRT showed that at an ER of 0.1 Ω, the UMDC achieved a maximum current of 143 mA and 86 mA, and TDS removal of 60.10 ± 6.50% and 42.50 ± 1.40% for saltwater and artificial seawater, respectively.…”
Section: External Resistance (Er)mentioning
confidence: 99%
“…Therefore, the effects of proton accumulation in the anolyte was diminished by setting back Rext to low external resistance at 1  to facilitate an easy flow of electrons from the anode to the cathode. Such higher flow of electrons enhanced the migration of ions from the desalination chamber to anode and cathode chambers, which ultimately increased the EC decrement (Chen et al, 2013). The migrated Clions neutralized the accumulated proton in the anolyte and reduced the effect of pH drop.…”
Section: Biofilm Enrichmentmentioning
confidence: 99%
“…This is mainly due to the precipitations of ions on the membrane leading to membrane scaling. Such precipitation of ions could decrease the whole reactor performance over time (Chen et al, 2013;Ma et al, 2015;Ebrahimi et al, 2018). Moreover, the rate of ions transportation through IEMs depends on the membrane microstructures.…”
Section: Introductionmentioning
confidence: 99%